2018
DOI: 10.3390/electronics7100214
|View full text |Cite
|
Sign up to set email alerts
|

A Control Strategy for Bidirectional Isolated 3-Phase Current-Fed Dual Active Bridge Converter

Abstract: This paper examines the characteristics of the zero voltage switching (ZVS) and zero voltage transition (ZVT) soft-switching applied in the 3-phase current fed dual active bridge (3P-CFDAB) converter, which combines the advantages of the dual active bridge (DAB) converter and current-fed full bridge (CFFB) converter. When an active clamp circuit is added to the CFFB converter, the circuit configuration of the DAB converter is shown in part of the entire circuit. This allows the use of pulse width modulation (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It can be seen that in operation at the duty cycle range 1/3 ≤ D < 2/3, the maximum current ripple value of the proposed topology is 0.0083 occurs at D = 1/2, where this value is one‐third compared with Jin and Liu 23 and half value compared with Bal et al 51 While in operation at duty cycle range 2/3 ≤ D < 1, the current ripple of studied topology is higher than that of the converter in Bal et al 52 ; when the duty cycle is equal to 5/6, and the normalized current ripple is equal to 0.0083. Furthermore, the current ripple of the previously proposed converters in previous studies 26 , 51 is higher than that of the proposed topology, according to the values shown in Figure 12A. Also, the normalized current ripple cancellation of the proposed topology occurs when the duty cycle is 1/3 and 2/3, which means that the proposed topology has a better dynamic response and smaller size inductor.…”
Section: Mathematical Analyses and Fundamental Equationsmentioning
confidence: 82%
See 1 more Smart Citation
“…It can be seen that in operation at the duty cycle range 1/3 ≤ D < 2/3, the maximum current ripple value of the proposed topology is 0.0083 occurs at D = 1/2, where this value is one‐third compared with Jin and Liu 23 and half value compared with Bal et al 51 While in operation at duty cycle range 2/3 ≤ D < 1, the current ripple of studied topology is higher than that of the converter in Bal et al 52 ; when the duty cycle is equal to 5/6, and the normalized current ripple is equal to 0.0083. Furthermore, the current ripple of the previously proposed converters in previous studies 26 , 51 is higher than that of the proposed topology, according to the values shown in Figure 12A. Also, the normalized current ripple cancellation of the proposed topology occurs when the duty cycle is 1/3 and 2/3, which means that the proposed topology has a better dynamic response and smaller size inductor.…”
Section: Mathematical Analyses and Fundamental Equationsmentioning
confidence: 82%
“…Moreover, there are two types of BDCs, which are nonisolated and isolated. Nonisolated TBDCs (NTBDCs) [27][28][29][30][31][32][33] configurations are simpler than isolated TBDCs (ITBDC) 22,23,[34][35][36] and can achieve better efficiency. However, galvanic isolation is required in many applications and mandatory by different national and international standards.…”
Section: Introductionmentioning
confidence: 99%
“…3.2 is the circuit diagram [16] of the door mechanism. The L293D device is a quadruple high-current half-H driver designed to provide bidirectional drive currents [17] of up to 600-mA at voltages from 4.5 V to 36 V. It is designed to drive inductive loads [18] such as relays, solenoids, DC and bipolar stepping motors, as well as high-current/high-voltage loads in positive-supply applications. The microcontroller through its P2.2 and P2.3 sends input to the motor drive.…”
Section: Door Mechanismmentioning
confidence: 99%
“…This problem can be solved by increasing the duty ratio gradually from 0 up to 50% at the initial soft start-up operation of the DAB converter [28,29]. When the SC module is charged and discharged by a DAB converter, it initially performs a soft start-up operation to maintain a stable PWM switching [30]. Unlike lithium-ion batteries, the SC module has a large potential difference during charging and discharging.…”
Section: Introductionmentioning
confidence: 99%